Análise físico-química e energética de briquetes de feijão guandu (Cajanus cajan) Silg 2009 submetidos à torrefação - Madalena , Lilian Cristina de Souza (2019)
Renewable energy sources are gaining more space in the global energy matrix every day. Lignocellulosic biomass, such as forest biomass, wood sawdust, urban pruning, agricultural waste, etc., could be better used if subjected to the processes available for the production of solid biofuels. Among the processes that can improve the energetic characteristics of the in Natura biomass, briquetting and roasting are highlighted. The pigeon pea has, being a woody forage, interesting physicochemical and energetic characteristic, besides good biomass production. The objective of this work was to analyze and evaluate the physicochemical and energetic properties of pigeon pea briquettes (Cajanus cajan) SILG 2009 in natura and subjected to roasting. The experiment was conducted on a laboratory scale, where they were tested as independent variables: temperature (200, 250 and 300 °c), heating rate (1.5; 3.0 and 4.5 °c/min.) and reaction time (1, 2 and 3 h) and as dependent variables: chemical characterization ( Lignin, Holocelulose, cellulose and hemicellulose contents), Immediate chemical analysis (moisture content, fixed carbon, volatile and ash materials), apparent and energetic density, superior calorific power. Treatment 6, with temperature of 300 º C, heating rate 4.5 º C/min. and residence time of 1 H stood out among the treatments. With a reduction of 46.3% of the volatile material content, an increase of 177.8% of fixed carbon content and increase of calorific power by 42.5%. It is concluded that the use of the briquetting process, associated with roasting, is only expanding the use of these residues, and boosting the consumption of this solid fuel. The present work was carried out with the support of the coordination of improvement of higher education personnel-Brazil (CAPES)-Financing code 001.